Heritability of Growth Traits of Simmental Cattle in Balai Pembibitan Ternak Unggul-Hijauan Pakan Ternak (BPTU-HPT), Padang Mengatas, West Sumatra, Indonesia - D. E. Putra; Sarbaini Sarbaini; T. Afriani; H. Suhada; F. Arlina (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2017)
This study is proposed to determine the heritability of growth traits of Simmental cattle in BPTU-HPT Padang Mengatas, West Sumatra. Data were collected by observations and measurements of the cattle in the field, completed by the secondary data from BPTU-HPT recorded from 2010 to 2016. Data for heritability were collected from 455 offsprings belonged to 15 sires. Weight and body size are two parameters used to estimate the heritability and breeding value, the heritability was analyzed between weaning and yearling age and breeding value was only calculated for weaning age. The data were analyzed by using paternal half-sib correlation method. The heritability between bulls and offspring was varied in weaning age, ranged from 0.24 to 0.97, and yearling age was showed high heritability in all parameters, ranged from 0.56 to 0.64. The heritability of weaning weight was 0.50 ± 0.19, weaning body size (shoulder height, body length and heart girth) was 0.97 ± 0.31; 0.24 ± 0.13; 0.44 ± 0.19, yearling weight was 0.56 ± 0.08 and yearling body size was 0.58 ± 0.08; 0.64 ± 0.09 and 0.56 ± 0.08 respectively. This result found that the highest heritability was shoulder height and the lowest heritability was body length. Relative breeding value above 0 represented by six sires with the highest breeding value was 37.12. Sires with the highest BV can be selected for future breeding in BPTU-HPT Padang Mengatas, while the lowest BV is recommended to be culled.